A=(3x-4)-(-2x+5)

Simple and best practice solution for A=(3x-4)-(-2x+5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for A=(3x-4)-(-2x+5) equation:



=(3A-4)-(-2A+5)
We move all terms to the left:
-((3A-4)-(-2A+5))=0
We calculate terms in parentheses: -((3A-4)-(-2A+5)), so:
(3A-4)-(-2A+5)
We get rid of parentheses
3A+2A-4-5
We add all the numbers together, and all the variables
5A-9
Back to the equation:
-(5A-9)
We get rid of parentheses
-5A+9=0
We move all terms containing A to the left, all other terms to the right
-5A=-9
A=-9/-5
A=1+4/5

See similar equations:

| F=6+12t | | 12x-11=5x+3 | | -6x-42+12x=90 | | 596-7x)+5(x-12)=0 | | -6+4r=6r | | x9-1=-10 | | 2h-7=12h-2h+3 | | 5(2x+9)=-17+52 | | 2,5x^2+4x=0 | | -3z=-4z+9 | | 1/8x+6=34 | | 5/3x+1/3x=222/3+6/3x | | G(x)=32/5x+55 | | 5/x=40/6= | | 42/g=6 | | 6(9x−10)+2(18−3x)=−8 | | -12+4m=-2-6(-4+m) | | 3^2-a=30 | | 9-8b=2 | | 0.5x-3=7.5 | | 7x-18+x=6 | | 6h-9=-9 | | 6+3b=14 | | 14d+20=20 | | 57p-10=30 | | 6+b/4=8 | | 6x-10/3=4x+8/7 | | 4-6a=2 | | 4m+-19=-15 | | 12g−9g=18 | | -5/8x=-20 | | 16s−10s=12 |

Equations solver categories